2023
DOI: 10.1111/apha.13918
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 prevents non‐alcoholic steatohepatitis through modulating mitochondrial quality control

Abstract: Aim Nonalcoholic steatohepatitis (NASH) is a severe form of nonalcoholic fatty liver disease (NAFLD) and lacks effective treatment options. Heme oxygenase‐1 (HO‐1) is a critical defense against oxidative stress and inflammation in the liver injury. This study aims to investigate the protective role and underlying mechanisms of HO‐1 in NASH pathogenesis. Methods The hepatocyte‐specific HO‐1 knockout (HO‐1HEPKO) mice on a C57BL/6J background (HO‐1fl/fl/Alb‐Cre) were generated and fed a high‐fat/western‐style die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…[2][3][4] However, in 2014, Jais et al created hepatocyte-specific HO-1 knockout mice they named Lhoko and showed the opposite, that is, HO-1 seemed to exert deleterious effects and promote inflammation in NAFLD. 5 This work demonstrated increased HO-1 mRNA expression in diet-induced fatty liver, similar to the present Li et al study, 1 which found that HO-1 mRNA levels were also significantly higher with high-fat feeding-induced NAFLD. However, the two studies have entirely different findings regarding the role of HO-1 in NAFLD.…”
Section: Powering the Powerhouse: Heme Oxygenase-1 Regulates Mitochon...supporting
confidence: 89%
See 4 more Smart Citations
“…[2][3][4] However, in 2014, Jais et al created hepatocyte-specific HO-1 knockout mice they named Lhoko and showed the opposite, that is, HO-1 seemed to exert deleterious effects and promote inflammation in NAFLD. 5 This work demonstrated increased HO-1 mRNA expression in diet-induced fatty liver, similar to the present Li et al study, 1 which found that HO-1 mRNA levels were also significantly higher with high-fat feeding-induced NAFLD. However, the two studies have entirely different findings regarding the role of HO-1 in NAFLD.…”
Section: Powering the Powerhouse: Heme Oxygenase-1 Regulates Mitochon...supporting
confidence: 89%
“…5 Jais et al crossed these animals with Alb-Cre transgenic mice generating the Lhoko mice, 5 which caused a frameshift in exon 3 and an early stop codon that resulted in a truncated peptide consisting of nine amino acids. One must wonder whether the truncated nine amino acid peptide originating from the HO-1 gene in the Lhoko mice might have some protective action causing a differential finding compared to the HO-1 HEPKO mice described by Li et al 1 The vast majority of the scientific literature has demonstrated the protective effects of HO-1 as a protector against oxidative stress and as an inhibitor of lipid accumulation with favorable effects on health and NAFLD (Figure 1).…”
Section: Powering the Powerhouse: Heme Oxygenase-1 Regulates Mitochon...mentioning
confidence: 99%
See 3 more Smart Citations